Revision of Tomosvaryella Aczél (Diptera: Pipunculidae) in the Middle East, with description of 19 new species - Motamedinia, Behnam; Skevington, Jeffrey H.; Kelso, Scott (Zootaxa, 2021)
The genus Tomosvaryella Aczél, 1939 is revised from the Middle East. Fifty-nine species are recorded and 19 of these are new to science: T. acantha Motamedinia & Skevington sp. nov., T. ampliasa Motamedinia & Skevington sp. nov., T. anahitae Motamedinia & Skevington sp. nov., T. bistounensis Motamedinia & Skevington sp. nov., T. cyprusensis Motamedinia & Skevington sp. nov., T. ellipiensis Motamedinia & Skevington sp. nov., T. emaratensis Motamedinia & Skevington sp. nov., T. hamounensis Motamedinia & Skevington sp. nov., T. kiansiae Motamedinia & Skevington sp. nov., T. nimroozensis Motamedinia & Skevington sp. nov., T. oshidae Motamedinia & Skevington sp. nov., T. osteodes Motamedinia & Skevington sp. nov., T. saudiensis Motamedinia & Skevington sp. nov., T. soziana Motamedinia & Skevington sp. nov., T. spinula Motamedinia & Skevington sp. nov., T. subtransvaalensis Motamedinia & Skevington sp. nov., T. susa Motamedinia & Skevington sp. nov., T. unicorna Motamedinia & Skevington sp. nov. and T. yemenensis Motamedinia & Skevington sp. nov. are described and illustrated based on sequence information from the mitochondrial COI barcoding gene and morphological parameters. DNA barcodes are provided for 37 of the 59 species. Descriptions of new species, diagnoses, distribution maps and an illustrated key for all species are provided.